PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PERINDUSTRIAN PROVINSI SULAWESI SELATAN - Nurlindah Nurlindah; Abd. Rahman Rahim (COMPETITIVENESS, 2018)
This study aims to find out and analyze the influence of competence, motivation and discipline of work on the performance of employees of the Industrial Office of South Sulawesi Province. The design used in this research is descriptive survey method with regression technique. The population in this study was 56 employees as many as 56 people. The data collection techniques used in this study are Konsioner and survey.The results of this study show that. competencies have an insignificant effect on employee performance. With P=0.4880.05 with a coefficient of 0.079, this indicates that the employee's work competency does not affect employee performance. Work motivation variables have a significant positive effect on employee performance with P=0.0000.05 with a coefficient value of 0.763 this shows that the work motivation in the Industrial Service of south Sulawesi province is getting better. discipline has a significant positive effect on employee performance with P= 0.006 0.05 with a coefficient of 0.168 this indicates that the discipline of work in the office of the Provincial Industry Office of South Sulawesi is getting better. It can be concluded that Work Motivation and Discipline is very influential on employee performance, because the success of an organization and achieving organizational goals is determined by employee performance. Keywords: Competence, Motivation, Discipline and Performance.